2018
DOI: 10.1128/jvi.00580-18
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of MicroRNA 711 Mediates HIV-1 Vpr Promotion of Kaposi's Sarcoma-Associated Herpesvirus Latency and Induction of Pro-proliferation and Pro-survival Cytokines by Targeting the Notch/NF-κB-Signaling Axis

Abstract: Coinfection with HIV-1 and Kaposi's sarcoma-associated herpesvirus (KSHV) often leads to AIDS-related malignancies, including Kaposi's sarcoma (KS) and primary effusion lymphoma (PEL). The interaction between HIV and KSHV plays a pivotal role in the progression of these malignancies. We have previously demonstrated that, by upregulating miR-942-5p, HIV-1 viral protein R (Vpr) inhibits KSHV lytic replication by targeting IκBα to activate the NF-κB signaling (Q. Yan, C. Shen, J. Qin, W. Li, M. Hu, H. Lu, D. Qin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 71 publications
0
11
0
Order By: Relevance
“…By attaching to a specific binding site on PTEN 3 UTR luciferase reporter, miR-718 decreased PTEN's tumor suppressor activity in a dose-dependent manner, thus activating the AKT/mTOR signaling pathway and therefore promoting cell proliferation and angiogenesis (Xue et al, 2014). On the same note, Yan et al have found that, in patients infected with both HIV-1 and KSHV, miR-942 and -711 were upregulated, both leading to an activation of the NF-κB signaling pathway, which, in turn, inhibited KSHV lytic replication (Yan et al, 2018). The NF-κB signaling network has previously been shown to be consistently activated during viral infections, promoting an inflammatory state as well as HIV persistence due to its ability to activate the viral transcription (Hiscott et al, 2001).…”
Section: Cellular Micrornas Involved In Cell Signaling Pathways Durinmentioning
confidence: 98%
“…By attaching to a specific binding site on PTEN 3 UTR luciferase reporter, miR-718 decreased PTEN's tumor suppressor activity in a dose-dependent manner, thus activating the AKT/mTOR signaling pathway and therefore promoting cell proliferation and angiogenesis (Xue et al, 2014). On the same note, Yan et al have found that, in patients infected with both HIV-1 and KSHV, miR-942 and -711 were upregulated, both leading to an activation of the NF-κB signaling pathway, which, in turn, inhibited KSHV lytic replication (Yan et al, 2018). The NF-κB signaling network has previously been shown to be consistently activated during viral infections, promoting an inflammatory state as well as HIV persistence due to its ability to activate the viral transcription (Hiscott et al, 2001).…”
Section: Cellular Micrornas Involved In Cell Signaling Pathways Durinmentioning
confidence: 98%
“…For cancers caused by infections of oncogenic viruses, HIV regulates both the replication of these viruses and the progression of their associated cancers (8). For example, HIV-encoded products Tat, Nef, and Vpr regulate KSHV replication and the functions of KSHV genes, resulting in enhanced cell migration, invasion, and angiogenesis (9)(10)(11)(12)(13)(14)(15). Moreover, long-term use of antiretroviral drugs in HIV patients is associated with an elevated risk of several cancers (16).…”
mentioning
confidence: 99%
“…This suggests that virus-virus interactions between KSHV and HIV are required for malignant transformation. Since the KS lesion is of endothelial cell origin and HIV does not directly infect endothelial cells, studies have focused on elucidating the circulating soluble HIV proteins that may potentiate neoplastic processes (24)(25)(26)(27)(43)(44)(45). Previous reports indicated that viral proteins secreted by HIV-infected cells may be taken up by KSHV-infected cells and consequently dysregulate the KSHV latent to lytic infection switch (39,46) and promote disease progression (24-27, 43, 45).…”
Section: Discussionmentioning
confidence: 99%